IMPROVEMENT OF DIGITAL IMAGE USING A COMBINATION OF ALPHA TRIMMED MEAN FILTER AND ARITHMETIC MEAN FILTER - Insidini Fawwaz; N P Dharshinni; Irfan Hindrawan (Sean Institute, 2022)
The development of technology at this time causes the provision of information to increase through social media. Many social media users convey information by including digital images. Digital images are very important in conveying the accuracy of information. However, digital images often experience various disturbances, such as decreased pixel quality, less sharpness, blurring, and the appearance of noise in the image. Noise contained in the image causes a decrease in image quality. Image degradation can be caused by uneven light intensity and can also be caused by dirt adhering to the camera lens. There are various types of noise found in digital images, including Salt And Pepper Noise, Speckle Noise, and Rayleigh Noise. There are many filtering methods that can improve digital images from noise interference. Some of them are the Mean Filter method, Geometric Mean Filter, Harmonic Mean Filter, Arithmetic Mean Filter, Median Filter, Midpoint filter, Alpha Trimmed Mean Filter and so on. Based on the research conducted, the combination of the Alpha Trimmed Mean Filter and Arithmetic Mean Filter methods can reduce Salt and Pepper noise, Speckle noise and Rayleigh noise better than the Alpha Trimmed Mean Filter and Arithmetic Mean Filter methods based on the MSE, RMSE and PSNR parameters.